1999
DOI: 10.1046/j.1365-3040.1999.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chilling temperature on photosynthetic rates, photosynthetic enzyme activities and metabolite levels in leaves of three sugarcane species

Abstract: The aim of this study was to investigate the mechanism of photosynthetic changes in sugarcane leaves in response to chilling temperature by using three species (Saccharum sinense R. cv. Yomitanzan, Saccharum sp. cv. NiF4 and Saccharum officinarum L. cv. Badira) differing in origin and cold sensitivity. Yomitanzan is native to subtropical areas, Badira is native to tropical areas and NiF4 is a hybrid species containing genes of both tropical and subtropical species. At exposure to chilling temperature (10°C), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 28 publications
2
51
0
4
Order By: Relevance
“…This is consistent with the observation that there are few amino acid changes that distinguish C 4 PPDK sequences among M. 3 giganteus, maize, and cold-intolerant sugar cane (Naidu et al, 2003). Previous analyses of sugar cane lines with different cold sensitivity (Du et al, 1999a) and Echinochloa crus-galli ecotypes from contrasting climates (Simon, 1996) also concluded that cold tolerance in those species is not due to the intrinsic properties of PPDK. The difference in crude extracts is therefore the result of either posttranslational modification or the presence of activators or inhibitors that affect the activity of the enzyme in leaf extracts.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is consistent with the observation that there are few amino acid changes that distinguish C 4 PPDK sequences among M. 3 giganteus, maize, and cold-intolerant sugar cane (Naidu et al, 2003). Previous analyses of sugar cane lines with different cold sensitivity (Du et al, 1999a) and Echinochloa crus-galli ecotypes from contrasting climates (Simon, 1996) also concluded that cold tolerance in those species is not due to the intrinsic properties of PPDK. The difference in crude extracts is therefore the result of either posttranslational modification or the presence of activators or inhibitors that affect the activity of the enzyme in leaf extracts.…”
Section: Discussionsupporting
confidence: 87%
“…The subunits dissociate between 10°C and 15°C, causing an increase in the energy of activation (E a ) and a loss of catalytic rate with further decline in temperature (Shirahashi et al, 1978;Ohta et al, 1996;Du et al, 1999b). In addition, the maximum extractable PPDK activity correlated well with cold tolerance in three Saccharum species (Du et al, 1999a) and across maize cultivars (Sugiyama and Boku, 1976). In contrast to the effects of temperature on the PPDK enzyme, there appears to be no correlation between thermal properties of other C 4 photosynthetic enzymes and differences in cold sensitivity of plant ecotypes (Du et al, 1999b;Hamel and Simon, 2000).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The cold sensitivity of PPDK in C 4 plants is well established and the mechanism of cold inactivation of PPDK is studied in detail [15,[17][18]. In contrast, the reports on cold sensitivity of PEPC have been quite conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…is an important tropical grass crop that suffers from abiotic stresses caused by low temperatures and drought (Robertson et al, 1999;Tai and Lentini, 2002;Silva et al, 2008). These stresses can reduce sugarcane photosynthetic rates considerably, and a decrease by more than 50% was observed after exposure to temperatures of 10ºC for 3 days (Du et al, 1999). This can lead to alterations in sugar quality and reduction in biomass.…”
Section: Introductionmentioning
confidence: 99%